Strategi Pemasaran Daya Tarik Wisata Untuk Meningkatkan Jumlah Kunjungan Wisatawan Ke Daya Tarik Wisata Sangeh Kabupaten Badung Provinsi Bali - Mahendrayani, I Gusti Ayu Putu Seri; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i02.p09, 2018)
Tourist attraction Sangeh is a tourist place on the island of Bali which is located in the village of Sangeh, District Abiansemal, Badung, Bali Province. Tourist attraction Sangeh present in the form of points ash long tail macaques, Pala Forest, and Pura Bukit Sari as its appeal. The number of tourists who visited Travel Attractions Sangeh from time to time experienced an increase after falling dramatically in 2012, amounting to 54 637 people, but the increase in the number of tourists is still quite slow and when compared with the visit of the peak that occurred in 2009 amounted to 225 672 people is still very low. The research aims to the right marketing strategic to increase rapidly tourists to visit Travel Attractions Sangeh.                        The method used in this study through questionnaires, observation, library research, documentation and interview with the manager. The data obtained were analyzed using descriptive analysis techniques were used to analyze the marketing mix and strategy using SWOT analysis as well as using a Likert scale to analyze the questionnaires were distributed.                   Results from this study is a marketing strategy that can be done to increase the number of tourists visiting tourist attraction Sangeh is creating branding tourist attraction sangeh as a natural tourist attraction quality, maintain the cleanliness and beauty of nature, promotion via the internet and brochures to introduce tourist attraction Sangeh to be better known by tourists as well as image building tourist attraction Sangeh to fix the problems that led to the number of visits in 2012 and then dropped dramatically in the next year began to increase but slowed impressed not know are like before 2012   Keywords : Marketing Strategy, Number of Visits, Tourist Attractions Sangeh